Prevalence of Fosfomycin Resistance Among Clinical Isolates Of Klebsiella Pneumoniae at a Tertiary Care Hospital in Bangladesh - Akter, Farhana; Shamsuzzaman, S M (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Fosfomycin, an old antimicrobial has aroused interest for the treatment of multidrug resistant infections. Unfortunately, the prevalence of fosfomycin resistance is increasing. Therefore, this study was done to investigate thepresence of fosfomycin resistance and identify the fosfomycin resistance genes by Polymerase Chain Reaction (PCR) among the clinical isolates of Klebsiella pneumoniae. Materials and methods: This cross-sectional study was conducted in the Department of Microbiology of Dhaka Medical College, Dhaka, Bangladesh from January 2021 to December 2021. K. pneumoniae was isolated and identified by culture, Gram staining and biochemical tests. Minimum Inhibitory Concentration (MIC) of fosfomycin was determined by agar dilution method.PCR was used to identifyfosfomycin resistance genes (fosA, fosA3, fosA4, fosA5, fosB,fosC, fosC2 and fosX). Results: Among 55 isolated K. pneumoniae, 10 (18.18%) were resistant to fosomycin detected by agar dilution method. MIC of fosfomycin showed a significant rise ranging from 256 to 4096 µg/ml.Out of 10 fosfomycin resistant K. pneumoniae, 8 (80%) were positive for fosA 5 followed by5 (50%) for fosA, 4 (40%) for fosA3, 3 (30%) for fosA4 and 2 (20%) were positive for fosB. Conclusion: This study showed that fosfomycin resistance has been increasing gradually leading to raised multidrug resistance demanding the implementation of effective antibiotic policy. JCMCTA 2025 ; 36 (1) : 88-92